Ion transmission through a dielectric hollow tip for scanning probe microscopy. (January 2019) - Mironov, B.N.; Aseyev, S.A.; Chekalin, S.V.
Abstract: We present a new concept for scanning probe microscopy characterization of molecular microstructures. It is based on a thin capillary using as a sharp tip to probe and map the morphology of a surface. In our experiment a collimated ion beam is formed by tungsten ions passing through a quartz tapered capillary with a 100-nm aperture and enters a 2D position-sensitive detector. We demonstrate that such ions are capable of producing the image of a dielectric nanoaperture in the case of low-dose ion beam. Ion transmission through a nanoscale capillary opens the door to observing photodesorption of large organic molecular ions with high spatially-element resolution using the combination of a hollow-tip vacuum scanner with time-of-flight mass spectrometer.